2021
DOI: 10.3389/fcell.2021.628103
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Exosomes in Oral Squamous Cell Carcinoma

Abstract: Oral cancer constitutes approximately 2% of all cancers, while the most common type, oral squamous cell carcinoma (OSCC) represents 90% of oral cancers. Although the treatment of OSCC has improved recently, it still has a high rate of local recurrence and poor prognosis, with a 5-year survival rate of only 50%. Advanced stage OSCC tends to metastasize to lymph nodes. Thus, exploring new therapeutic strategies for OSCC is therefore an urgent priority. Exosomes, the small membrane vesicles derived from endosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 137 publications
(100 reference statements)
0
35
0
Order By: Relevance
“…Exosomes, which are small membrane vesicles released by various cells, including tumor cells, can be taken up by parent and recipient cells, consequently affecting their function and activity through included materials, such as lipids, proteins, and nucleic acids from their cell of origin 5 . Studies have shown that tumor‐derived exosomes affect tumorigenesis, tumor progression, and metastasis by exhibiting immunosuppressive properties, facilitating tumor invasion and metastasis, stimulating tumor cell proliferation, or inducing drug resistance 6,7 . We also previously demonstrated that OSCC cell‐derived exosomes taken up by OSCC cells themselves significantly promoted proliferation, migration, invasion, and growth of tumor xenografts implanted into nude mice through the activation of the phosphatidylinositol 3‐kinase (PI3K)/Akt, MAPK/extracellular signal regulated kinase (ERK), JNK‐1/2 pathways 8 .…”
Section: Introductionmentioning
confidence: 94%
“…Exosomes, which are small membrane vesicles released by various cells, including tumor cells, can be taken up by parent and recipient cells, consequently affecting their function and activity through included materials, such as lipids, proteins, and nucleic acids from their cell of origin 5 . Studies have shown that tumor‐derived exosomes affect tumorigenesis, tumor progression, and metastasis by exhibiting immunosuppressive properties, facilitating tumor invasion and metastasis, stimulating tumor cell proliferation, or inducing drug resistance 6,7 . We also previously demonstrated that OSCC cell‐derived exosomes taken up by OSCC cells themselves significantly promoted proliferation, migration, invasion, and growth of tumor xenografts implanted into nude mice through the activation of the phosphatidylinositol 3‐kinase (PI3K)/Akt, MAPK/extracellular signal regulated kinase (ERK), JNK‐1/2 pathways 8 .…”
Section: Introductionmentioning
confidence: 94%
“…To the contrary of most reported findings, Melnik and Schmitz (73) pointed out that continuous intake of milk exosomes may pose a risk for chronic diseases including obesity, type 2 diabetes mellitus, osteoporosis, Parkinson's disease, and common cancers, mainly due to the miRNAs inside the exosomes: such as miR-148a which suppress inhibitor of adipogenesis, miR-29b which belongs the diabetogenic miR family, miR-155 which can promote the initiation and progression of Parkinson's disease in humans, and miR-21which promotes tumor progression. The miRNA-21, which was observed in milk exosomes, can enhance mTOC1driven metabolic processes by attenuating the inhibitory effects of various tumor suppressor proteins on mTORC1-signaling (85,86). The authors mentioned that as human breast milk is the ideal food for infant, persistent high cow milk signaling during adolescence and adulthood may promote diseases of civilization.…”
Section: Future Researchmentioning
confidence: 99%
“…Despite the fact that great advances have been made in surgical techniques and chemoradiation therapy, the 5-year survival rate for OSCC patients remains very low [4,5]. The inability for diagnosing in the preliminary phase refers to the main reason for the unfavorable outcome of OSCC cases [6,7]. It has been confirmed the involvements of multiple genetic and epigenetic abnormality in OSCC progressions, but the molecular mechanisms involved in OSCC tumorigenesis remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%